2007
DOI: 10.1007/s00415-007-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 mutation in Taiwanese early-onset parkinsonism

Abstract: The PINK1 gene mutation is probably the second most common genetic cause of early-onset Parkinson's disease (EOPD). The frequency and the characteristics of the PINK1 mutation in the Taiwanese population are unknown. This study was designed to investigate the genotype, phenotype and dopaminergic function of PINK1 in a cohort of EOPD patients. The genetic settings were to detect the PINK1 gene mutations in 138 EOPD patients and in 191 controls. Using the (99m)Tc-TRODAT-1 (TRODAT) scan, we investigated the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 30 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…A homozygous stop mutation in two Italian families and a homozygous missense mutation in a consanguineous Spanish kindred. Mutations in PINK1 are usually private loss of function changes and have been found to be the second most common cause of early onset autosomal recessive PD [76, 89, 130]. As with PARK2 mutations, there has been speculation about the role of single PINK1 heterozygous mutations as a risk factor for PD.…”
Section: Autosomal Recessive Causes Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…A homozygous stop mutation in two Italian families and a homozygous missense mutation in a consanguineous Spanish kindred. Mutations in PINK1 are usually private loss of function changes and have been found to be the second most common cause of early onset autosomal recessive PD [76, 89, 130]. As with PARK2 mutations, there has been speculation about the role of single PINK1 heterozygous mutations as a risk factor for PD.…”
Section: Autosomal Recessive Causes Of Pdmentioning
confidence: 99%
“…Clinically, patients usually have a later age at onset in the 40s and 50s but otherwise are similar to the PD associated with PARK2 mutations, displaying slowly progressive levodopa-responsive disease. Atypical features are often observed and include prominent dystonia, sleep benefit and pyramidal signs [7, 14, 130]. …”
Section: Autosomal Recessive Causes Of Pdmentioning
confidence: 99%
“…About 10% of cases are characterized by early onset, and these mostly occur in familial clusters (Mizuno et al 2001). Development of parkinsonian syndrome in such individuals has been attributed to mutations in several recently identified genes, including parkin, Leucine-rich repeat kinase 2 (LRRK2), á-synuclein, PINK-1, or DJ-1 (Polymeropoulos et al 1997; Sun et al 2006; Bonifati et al 2008; Weng et al 2007; Abou-Sleiman et al 2003; Jiang et al 2007). In contrast, development of idiopathic PD may represent the final outcome of a complex set of interactions among the innate vulnerabilities of the nigro-striatal DA system, potential genetic predisposition, and exposure to environmental toxins.…”
Section: Parkinson's Disease: a Chronic Inflammatory Progressive Neumentioning
confidence: 99%
“…SNCA , Parkin , PINK1 , DJ-1 , LRRK2, and ATP13A2 have been identified to be the causative genes for familial and early onset Parkinson's disease (EOPD) [51]. A 99m Tc-TRODAT-1 scan revealed that patients with the PINK1 mutation displayed a rather even, symmetrical reduction of dopamine uptake, whereas patients with late-onset Parkinson's disease (LOPD) displayed a dominant decline in dopamine uptake in the putamen [56]. The contribution of genetic variants in ATP13A2 to Parkinson's disease of Taiwanese patients was investigated with 99m Tc-TRODAT-1 SPECT, showing that the striatal uptake of patients carrying the variants of G1014S and A746T were similar to that of idiopathic Parkinson's disease [51].…”
Section: Parkinson's Disease and Other Movement Disordersmentioning
confidence: 99%